2007
DOI: 10.1007/s11661-007-9091-z
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Parameters and Local Lattice Distortions in fcc-Ni Solutions

Abstract: The lattice parameters and the local lattice distortions around solute atoms in fcc-Ni solutions were studied using first-principles calculations. The solute atoms considered include Al, Co, Cr, Hf, Mo, Nb, Re, Ru, Ta, Ti, and W. The calculations were performed using supercells with 1 solute atom and 107 solvent atoms. It is found that the atomic size difference, the electronic interactions, and the magnetic spin relations between the solute and solvent atoms all contribute to the lattice distortions. Based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…This suggests that the influence on the lattice distortion from the introduced Sn atoms are mainly constrained to the 1NN atoms and is much weaker for farther atoms. Meanwhile, the distortions do not vary evidently with Sn contents and this is consistent with other Ni or Al based solid solutions[1,2].The measured thermal expansions dL/L 0 for Ni 92 Sn 8 and Ni 96 Sn 4 in two dilatometer cycles, one for the as-cast sample and the other for the annealed sample, are illustrated in…”
supporting
confidence: 85%
See 2 more Smart Citations
“…This suggests that the influence on the lattice distortion from the introduced Sn atoms are mainly constrained to the 1NN atoms and is much weaker for farther atoms. Meanwhile, the distortions do not vary evidently with Sn contents and this is consistent with other Ni or Al based solid solutions[1,2].The measured thermal expansions dL/L 0 for Ni 92 Sn 8 and Ni 96 Sn 4 in two dilatometer cycles, one for the as-cast sample and the other for the annealed sample, are illustrated in…”
supporting
confidence: 85%
“…This value is larger than those for most Ni based solid solutions [2,13] since Sn atom is larger than those solute atoms. Additionally, some referenced data for the solid solutions formed in long-time annealed and quenched Ni-Sn alloys are presented for comparison [8].…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Atomic-resolution EDS, in Figure 1(b), reveals that Cr predominantly occupies the Al sub-lattice in the c 0 phase, in agreement with recent atom probe tomography experiments 15,16 and first-principles calculations. 17 At the atomic scale, a representative c 0 /c interface is shown in Figure 1(c), where the two regions can be distinguished by the presence of the ordered Al/Cr sub-lattice atom column intensities (dark). In contrast, all atom columns in the c region exhibit similar intensity because a random solid solution is formed on a face-centered cubic lattice.…”
mentioning
confidence: 99%
“…As more number of solute particles goes into solution, the lattice parameter of nickel increases. Wang et al 20 reported that for FCCNi solutions the lattice parameter of solvent increased when solute atoms of larger atomic radius were added. Sharma et al 21 reported about the increase in lattice parameter in the case of mechanical milling of pure KCl powder under vacuum.…”
Section: Xrd Studiesmentioning
confidence: 99%